The concept of Itqan and its role in Muslim - Haji Adam, Ibrahim A.; Shuriye, Abdi Omar (2008)
Professional Ethics which concern one’s conduct of behavior and practice when carrying out professional work needs Itqan. The word Itqan is an Arabic word which has a close meaning to the English word perfection. Islam as a perfect and comprehensive religion set the bases for quality work. The order, discipline, accuracy, beautiful work, well thought out tasks and justice are all part of quality Islamic work and performance. Quran as the final divine revelation from Allah provides a code of conduct for every believer and is the commandment and warrant for him to be committed in his/her work and be sincere about it [5]. Adhering to the Quranic teachings on itqan equips the Muslim professional an effective approach to problem-solving preceded by steady and thorough examination before undertaking an activity and enables the Muslim to tackle problems in an orderly and disciplined manner. This prompts us to the institutionalization of Codes of Conduct and Codes of Practice is common with many professional bodies for their members to observe. This paper attempts in this concept and its role in the Muslim life.